2017
DOI: 10.1002/apj.2078
|View full text |Cite
|
Sign up to set email alerts
|

Sulfation roasting characteristics of copper‐bearing materials

Abstract: In this study, the sulfation roasting characteristics of copper-bearing ore and its flotation products as chalcopyrite concentrate and tailings were investigated in detail. For this aim, the roasting-leaching experiments and thermal analyses were conducted on the samples. As a result of the leaching of sulfated products obtained from the roasting experiments, the maximum Cu extractions were achieved as 94.7%, 99.5% and 82.7%, for run of mine, chalcopyrite concentrate and the flotation tailings, at the roasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Although the majority of research present in the literature [17,22,23] is about the chemistry and thermodynamics of the sulfation roasting process using synthetic mixtures as well as natural chalcopyrite concentrates, studies about the thermodynamic and kinetic behavior of low-grade and complex secondary metal sources are very limited. Thus, Ozer et al (2017) stated that it was not possible to obtain a selective sulfation without any additive between copper and iron in the roasting of tailings that had been stored for a long time and oxidized under atmospheric conditions, at any temperature due to their heterogeneous structure and mineralogicalchemical compositions [24]. [21] In order to improve the sulfation conditions and obtain higher selectivity, a number of promoters such as Fe 2 [23,[25][26][27][28][29].…”
Section: J Min Metall Sect B-metall 55 (3) B (2019) 315 -324mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of research present in the literature [17,22,23] is about the chemistry and thermodynamics of the sulfation roasting process using synthetic mixtures as well as natural chalcopyrite concentrates, studies about the thermodynamic and kinetic behavior of low-grade and complex secondary metal sources are very limited. Thus, Ozer et al (2017) stated that it was not possible to obtain a selective sulfation without any additive between copper and iron in the roasting of tailings that had been stored for a long time and oxidized under atmospheric conditions, at any temperature due to their heterogeneous structure and mineralogicalchemical compositions [24]. [21] In order to improve the sulfation conditions and obtain higher selectivity, a number of promoters such as Fe 2 [23,[25][26][27][28][29].…”
Section: J Min Metall Sect B-metall 55 (3) B (2019) 315 -324mentioning
confidence: 99%
“…Previous studies showed that these kinds of materials had different roasting behavior due to their mineralogical and chemical structures. It was also concluded that the decomposition of non-ferrous metal sulfates took place at a lower temperature, similar to ferrous sulfates [24]. Hence, it is worth noting that, during the recovery of copper and cobalt from that type of material, the most important issue is to prevent iron dissolution during leaching by selective sulfation [10,11].…”
Section: Leaching Following Roastingmentioning
confidence: 99%
“…In the diagram, the double oxides of copper and iron have been omitted. Considering the decomposition phenomena and energy-saving aspect, as well as some previous roasting studies, 8,33 600°C was selected as the set temperature for the experiments.…”
Section: Thermodynamicsmentioning
confidence: 99%
“…However, for low-grade ores and complex copper-bearing materials, it is often unfeasible to produce copper concentrates with the target assay for smelting. 8 What is even more relevant is that uncontrolled off-gas and fugitive emissions from pyrometallurgical plants may cause serious pollution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation